2021
DOI: 10.1111/dech.12640
|View full text |Cite
|
Sign up to set email alerts
|

Open Access, Plan S and ‘Radically Liberatory’ Forms of Academic Freedom

Abstract: This opinion piece interrogates the position that open access policies infringe academic freedom. Through an analysis of the objections to open access policies (specifically Plan S) that draw on academic freedom as their primary concern, the article illustrates the shortcomings of foregrounding a negative conception of academic freedom that primarily seeks to protect the fortunate few in stable academic employment within wealthy countries. Although Plan S contains many regressive and undesirable elements, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Samuel Moore (2021) posited that academic freedom arguments against OA were biased toward a minority of researchers in the developed world and considered OA in terms of social justice. He concluded that OA "works towards a more socially just global university system that is emancipatory from the inequalities of neoliberal capitalism and helps foster collectivity, experimentation and care" (p. 11).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Samuel Moore (2021) posited that academic freedom arguments against OA were biased toward a minority of researchers in the developed world and considered OA in terms of social justice. He concluded that OA "works towards a more socially just global university system that is emancipatory from the inequalities of neoliberal capitalism and helps foster collectivity, experimentation and care" (p. 11).…”
Section: Literature Reviewmentioning
confidence: 99%
“…But such dialectics is a delicate model and it seems to be rather absent in the heated debate on academic freedom. Whether or not it is coercion or freedom: Plan S does not achieve to address issues of Global equality so that even progressive OA advocates show sympathies with the objections to Plan S (Moore, 2021). It is guided by a non-inclusive perspective, on a both disciplinary and Global level (Istratii and Demeter, 2020).…”
Section: Large-scale Transformations As Narrow Accessibility: Plan Smentioning
confidence: 99%
“…We contend that scholars around the world should be free to choose communicative means for their/our work without concern for the pressures of academic evaluation regimes and/or the hegemonic ideologies of English. This position is grounded in the principles of academic freedom and linguistic human rights that do or should underpin scholarly work (Moore, 2021; Skutnabb-Kangas, 2012).…”
Section: Introductionmentioning
confidence: 99%